Graded balloon atrial septostomy for palliation of congenital pulmonary hypertension in a dog: A case report. (26th November 2019) - Allen, Justin; Peterson, Nathan; Barrett, Kirstie; Llamas, Anthony
Abstract: Case Description: A 6‐month‐old intact female Maltese dog was presented for acute onset of syncope. Clinical Findings: The dog was presented for collapse upon excitement and exercise. It collapsed at discharge and suffered cardiopulmonary arrest. Echocardiography after resuscitation indicated severe pulmonary hypertension without evidence of intracardiac or extracardiac shunting. A presumptive diagnosis of congenital pulmonary hypertension was made. Treatment and Outcome: Initial treatment with sildenafil was effective at relieving syncope, but the extent of pulmonary hypertension as determined by serial echocardiography was unchanged. Graded balloon atrial septostomy was performed as a palliative procedure. Follow‐up echocardiography identified a patent interatrial communication with bidirectional shunting. The dog remained asymptomatic 18 months after treatment. Clinical Relevance: To the best of our knowledge, this study is the first report in the veterinary literature of graded balloon atrial septostomy performed for therapeutic purposes. Further studies are required to determine if this palliative procedure is a beneficial treatment option for dogs with congenital or severe refractory pulmonary hypertension.